Detection and risk factor analysis of avian colibacillosis associated with colistin-resistant Escherichia coli and Klebsiella pneumoniae - Saeed, Muhammad Adnan; Asif, Haseeb; Ehtisham-ul-Haque, Syed; Khan, Aman Ullah; Rehman, Aziz ur; Rehman, Aiman; Rafique, Muhammad Kamran; Ahmed, Ishtiaq; Qamar, Muhammad Fiaz; Tomaso, Herbert; El-Adawy, Hosny (Frontiers in Veterinary Science, 2025)
Colibacillosis associated with colistin-resistant avian pathogenic Escherichia coli (E. coli) poses a threat to both food security and public health. The potential horizontal transmission of mobilized colistin-resistant (mcr) genes facilitates the co-emergence of Klebsiella pneumoniae. This study aimed to determine the prevalence, molecular detection, analyze the antibiogram and identify associated risk factors for colistin-resistant E. coli and Klebsiella pneumoniae isolated from broiler chicken in three districts of Punjab province, Pakistan. In total, 230 visceral organ samples were collected from 13 different chicken farms located in Sargodha, Jhang and Toba Tek Singh in Pakistan. Following isolation, the broth microdilution test was used to confirm phenotypic colistin resistance. Polymerase chain reaction was used to detect mcr-1 and mcr-2 genes associated with colistin resistance. Antimicrobial susceptibility test against 11 antibiotics was performed using the Kirby-Bauer disk diffusion method. Risk factors associated with colistin-resistant bacteria, including host attributes, farm management practices, environmental and agent characteristics, were analyzed. The prevalence of colistin-resistant E. coli and K. pneumoniae was 24.78% (95% CI, 19.6–30.7%) and 3.04% (95% CI, 1.5–6.1%), respectively. The prevalence of colistin-resistant E. coli varied between cities at 42, 23.61 and 5.55% for Jhang, Sargodha and Toba Tek Singh, respectively. The detection frequency of mcr-1 gene, 42.1% (24/57), was significantly (p < 0.01) higher than that of the mcr-2 gene, 14.03% (8/57). Phylogenetic analysis of lipid A phosphoethanolamine transferase sequences revealed greater similarity with mcr-1.5 variant. Isolates were found resistant to amoxicillin-clavulanic acid (84.21%), cefotaxime (70.17%), and trimethoprim-sulfamethoxazole (73.68%). The multivariate logistic regression predicted preceding viral infection of the respiratory tract as a significant association (OR = 4.808, p < 0.01), whereas daily removal/culling of dead/diseased chicken (OR = 0.308, p = 0.01) was a protective factor against the emergence of colistin-resistant strains. These findings indicate that the emergence of colistin-resistant strains deteriorate colibacillosis control efforts in poultry and serves as a possible reservoir for zoonotic infections.